Prospects of Halal Tourism Development in West Aceh District - Dista Setya Ningsih; Dyah Lituhayu; Budi Puspo Priyadi; Retno Sunu Astuti (Universitas Teuku Umar, 2022)
Halal Tourism is one of the sectors that is now expected to make a major contribution to the economy of a country. The concept of halal tourism aims to provide tourism services based on Islamic law. Not only Muslim countries are aggressively developing Halal Tourism, but several other non-Muslim countries are also now competing to open Halal Tourism packages, this is realized by a large number of the Muslim population in the world. Indonesia is no exception, especially Aceh, which is also currently developing Halal Tourism with all the potential it has so it is expected to become the world's main destination for Halal Tourism. This study aims to determine the prospects and challenges in developing Halal Tourism in West Aceh Regency. This research uses descriptive qualitative research methods using literature studies. The results of the study indicate that Aceh Barat Regency in developing Halal Tourism has collaborated with relevant agencies and stakeholders and provides services based on Islamic Sharia. The challenge of West Aceh Regency in developing Halal Tourism is to carry out strong collaboration between the central government, local governments, and industry players in the development of halal tourism, both related to promotion, branding, improvement of supporting facilities and infrastructure as well as efforts to change the mindset of the community and business actors regarding the importance of Developing Halal tourism